Towards the identification of ecological management units: A multidisciplinary approach for the effective management of bottlenose dolphins in the southern Iberian Peninsula. Issue 1 (2nd August 2017) - Giménez, Joan; Louis, Marie; Barón, Enrique; Ramírez, Francisco; Verborgh, Philippe; Gauffier, Pauline; Esteban, Ruth; Eljarrat, Ethel; Barceló, Damià; G. Forero, Manuela; de Stephanis, Renaud
Abstract: Determining discrete and demographically independent management units within wildlife populations is critical for their effective management and conservation. However, there is a lack of consensus on the most appropriate criteria to delimit such management units. A multi‐disciplinary, multi‐scale approach that combines tools informing in the short‐term (i.e. photo‐identification), with mid‐term ecological tracers (stable isotopes – δ 13 C, δ 15 N and δ 34 S– and persistent organic pollutants –POPs–), and mid‐ to long‐term genetic markers (microsatellites and mitochondrial DNA), was used to define management units within bottlenose dolphins ( Tursiops truncatus ) inhabiting the southern Iberian Peninsula. Although genetically indistinguishable, individuals inhabiting the Strait of Gibraltar and the Gulf of Cadiz showed differences in their isotopic composition and the concentrations of certain POPs. Accordingly, the lack of photographic recaptures between the two sites pointed to the existence of at least two different ecological management units that segregate spatially and may require different conservation strategies. Different time‐scale approaches can reveal different management units. The results highlighted the use of medium‐ and short‐term approaches for properly identifying ecologically different units for effective management and conservation. Furthermore, these results have important management implications as European legislation promotes specific management plans for this species.